Knowledge and practices of cervical cancer screening among married women in a semi-urban population of Ludhiana, Punjab - Niji Rachel Varughese; Clarence James Samuel; Pratiba Dabas (Wolters Kluwer Medknow Publications, 2016)
Background and Objectives: Cervical cancer is a leading cause of cancer mortality among women in India. Hence, the objectives of this study were to find out the perception of women towards cervical cancer and assess their health-seeking behavior for screening. Methodology: A cross-sectional study was conducted from November to December 2009 among married women above 15 years of age by systematic random sampling of households in Field Ganj, Ludhiana, India. Information was gathered by a questionnaire assessing the knowledge, attitude, and practices regarding cervical cancer. Results: Of the 304 women interviewed, 28.9% (88) had heard of cervical cancer and 12.2% (37) knew it could be preventable. Only 4.3% (13) of the women had heard about Pap smear. Interpretation and Conclusions: Inadequate knowledge about cervical cancer and Pap smear is the greatest obstacle to effective screening. Identifying individual and community-level barriers is important in increasing cervical cancer screening.